PENGARUH KUALITAS PRODUK, LAYANAN DAN RAGAM PRODUK TERHADAP KEPUTUSAN PEMBELIAN THERMOCOUPLE DI PT. FINE LEVEL INDONESIA - Muhammad Zulkifli Permadani (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
This study entitled The Effect of Product Quality, Service and Product Variety on Thermocouple Purchase Decisions at PT. Fine Level Indonesia This study aims to determine and analyze the quality of products, services and product variety on the thermocouple purchasing decisions at PT. Indonesian Fine Level. The population in this study were all consumers of PT. Indonesian Fine Level. Collecting data using a questionnaire with a non-probability sampling technique, namely accidental sampling with 100 respondents. The results of this study obtained the following conclusions: (1) From the partial test or t test, it shows that the Product Quality variable (X1) produces a t-count of 0.790 if referring to the indicator results that t-count 0.790<t- table 1.66023 and also the significance value is 0.432>0.05, which means that H1 is rejected. In other words, the Product Quality variable has no partial effect on the Y (Purchase Decision) Thermocouple variable at PT. Fine Level Indonesia. (2) From the partial test or t test, it shows that Variable X2 (Quality of Service) produces a t-count of 5.155 if it refers to the result indicator that t-count 5.155>t-table 1.66023 and also the significance value is 0.000<0.05 which means that H2 is accepted. In other words, the service quality variable has a partial effect on the Y (Purchase Decision) Thermocouple variable at PT. Fine Level Indonesia. (3). From the partial test or t test, it shows that Variable X3 (Variety of Products) produces a t-count of 3.944 if it refers to the result indicator that t-count is 3.944>t-table 1.66023 and also the significance value is 0.000<0.05, which means that H3 is accepted. in other words, the Product Variety variable has a partial effect on the Y (Purchase Decision) Thermocouple variable at PT. Fine Level Indonesia.